Evaluation of Allostatic Load as a Marker of Chronic Stress in Children and the Importance of Excess Weight - Valeria Calcaterra; Federica Vinci; Giulia Casari; Gloria Pelizzo; Annalisa de Silvestri; Mara De Amici; Riccardo Albertini; Corrado Regalbuto; Chiara Montalbano; Daniela Larizza; Hellas Cena; Hellas Cena (Frontiers Media S.A., 2019)
Introduction: Allostatic load (AL) refers to the physiological response associated with the burden of chronic stress. Excessive weight is an important source of physiological stress that promotes a detrimental chronic low-inflammation state. In order to define a correlation between cumulative biological dysregulation and excess weight, we measured AL scores in a pediatric population.Patients and Methods: We enrolled 164 children and adolescents (11.89 ± 3.89). According to their body mass index (BMI) threshold, subjects were classified as normal in the BMI < 75th percentile, overweight in the BMI 75-95th percentile or obese in the BMI >95th percentile. Data based on 16 biomarkers were used to create the AL score. A dichotomous outcome for high AL was defined in those who had more than four dysregulated components.Results: High AL was noted in 88/164 subjects (53.65%), without significant differences between genders (p = 0.07) or pubertal status (p = 0.10). Subjects with a high AL, in addition to a higher BMI (p < 0.001), showed higher WC and WC/HtR (p < 0.001), triglycerides (p = 0.002), fasting blood glucose (p = 0.03), insulin resistance (p < 0.001), systolic (p < 0.001) and diastolic blood pressure (p = 0.001), GGT (p = 0.01), PCR (p = 0.01), and calprotectin (p < 0.01) as well as lower HDL cholesterol (p = 0.002) than subjects with a low AL. The rate of the cumulative biological dysregulation increased progressively with increases in BMI (p < 0.001).Conclusions: A high AL was associated with excess weight. AL may be considered a significant factor correlated with increased morbidity in children who are overweight/obese.